698 A Systematic Review of Smartphone Applications for Enhanced Recovery After Surgery (ERAS) Following Colorectal Surgery. (4th May 2021) - Aseem, R; Cribb, E; Liccardo, F; Daulatzai, N; Smith, J; Pawa, N
Abstract: Introduction: Length of stay (LOS) following colorectal surgery has reduced due to enhanced recovery after surgery (ERAS) programs. Telemedicine has shown potential for patients to remotely access support, communicate progress with their medical team and enhance patient empowerment. We conducted a systematic review of smartphone applications for ERAS following colorectal surgery measuring patient outcomes and experience. Method: The review was performed adhering to PRISMA guidelines, using search terms pertaining to ERAS, colorectal surgery, and mobile applications via electronic databases. All peer-reviewed English articles were assessed for inclusion and quality by two reviewers. A qualitative analysis was conducted to evaluate methodologies, patient experience, and outcomes. Results: 206 abstracts were identified from which 5 articles (2 RCTs and 3 cohorts) were included in the analysis. Studies surveyed patient adherence to ERAS, LOS, readmission, intra and postoperative complications. Four studies recorded patient satisfaction, whilst one assessed quality of life and application validation. Conclusions: The review highlights paucity in the use of smartphone applications after ERAS in colorectal surgery but demonstrates high patient satisfaction levels. Service delivery in the NHS has increasingly moved to a virtual platform during the coronavirus pandemic. More research and engagement in the development and use of smartphone applications would enhance care for patients.